Desadaptação apical em obturação retrógrada em função do método de preparo e material - Fraga, Hálisson Rocha (2007)
The objective of the present work was to evaluate the apical desadaptation in function of root end preparation method and the filling material. Forty eight roots palatine of molars had your canals preparation by step back technique and obturated by cone unique technique. After obturation the root were included in acrylic resin exception 2mm of apical portion. The 2mm of apical root were apicoectomized and the roots were divided into two groups according root end preparation method: group 1: root end preparation with ultrason and diamond tips (S12 900D); group 2: root end preparation with bur 2 and low rotation. After the apical preparation the groups were divided into two subgroups according filling material: subgroup 1A: root end filling with MTA; subgroup 1B: root end filling with Sealer 26; subgroup 2A: root end filling with MTA; subgroup 2B: root end filling with Sealer 26. Concluded the root end filling the roots were immersed in deionizide water during 72 hours at 37ºC. After this period, the block of resin with the roots were dried and metalized and evaluated at scanning electron microscopic with 50X magnification. The phomicrographs were digitalized and at Image tools program the apical desadaptation area was measured. The results showed no significant differences at the comparison between root end preparation method and the kind of filling material. It was concluded the root end method preparation and the kind of filling material didn t influence at apical desadaptation at retrograde obturation.